A neuro-computational model of sequence learning in macaques: the Simultaneous Chaining Paradigm. (August 2017) - Gasser, Brad; Arbib, Michael A
We present a novel model, SCP1, of monkey sequence learning that takes the processes of stimulus recognition and motor planning seriously in addressing a robust dataset on list learning obtained through the Simultaneous Chaining Paradigm (SCP). Strikingly, SCP violates stimulus-response (S-R) mappings in that after several different lists are learned, monkeys are able to conserve this learning on a new list which is "conserved" in the sense that the j th element is specified as the j th element of any one of the previously learned lists. We demonstrate list acquisition as a result of multiple concurrent learning processes that together contribute to competent performance. In addition to reproducing behavioral results, we offer observations linking the work to macaque neurophysiology.